Online Classes and Motivation of Special Students at Higher Education Level during Covid-19: Phenomenological Study of Inclusive Education - Uzma Mazhar, (PJE, 2023)
This phenomenologicalstudy was conducted during the COVID19 outbreak to explore the impact of the pandemic situation on physically special students studying at university level. Special emphasis was given to the aspect of motivation of special students at higher levels during COVID-19. For this purpose, a sample of 19 students from two universities of Islamabad, Pakistan was selected. The required dat